The reality of the use of information and communications technology (ICT) in the open education system at Hama University from the perspective of students. "The kindergarten program at the Faculty of Education as a model" (Journal of Hama University, 2019)
The current study aims to examine the reality of the use of information and communications technology (ICT) at the university of open education at Hama university from the perspective of students, and study the effect of each variable (Gender, age of student) on student responses. The researcher used a descriptive analytical method in order to achieve the objectives of the study, by depending on the study tool, which consisted of a questionnaire distributed to the study sample of 60 students to know their responses towards the reality of the use of information and communications technology (ICT) in the open education system at Hama University.• The reality of the use of information and communications technology (ICT) in the open education system from the perspective of students is of the intermediate level.• There are no statistically significant differences between the average responses of students to the reality of the use of information and communications technology (ICT) in the open education system depending on the gender variable or on the age variable of the student.• The most important problems that prevent the use of information and communications technology (ICT) is the lack of information communications technology services.The most important factor in the development of the use of (ICT) in the open education system is providing facilities for the use of the fields of information and communications technology by students and faculty members